2018
DOI: 10.1016/j.arth.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Internet Promotion of Direct Anterior Approach Total Hip Arthroplasty by Members of the American Association of Hip and Knee Surgeons

Abstract: Over one-fifth of AAHKS members promoted the DAA on the internet. Member websites claimed DAA benefits such as faster recovery and decreased pain approximately 9 times more frequently than any potential risk of the procedure (P < .001). While AAHKS policy does not regulate member marketing, it is the responsibility of all orthopedic surgeons to disseminate accurate, validated information concerning the procedures we perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Nonetheless the early outcomes are making the approach increasingly attractive and popular to both surgeons and patients, especially in light of the tendency to underplay the potential risks in favour of the benefits that was observed in a recent survey amongst US surgeons. 88 As with most minimally invasive surgical techniques, a great deal of training and skill is required in order to be able to enjoy the advantages and avoid the potentially catastrophic complications. The learning curve is inevitable, as with any new skill or technique, and the early results appear to be surgeon-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless the early outcomes are making the approach increasingly attractive and popular to both surgeons and patients, especially in light of the tendency to underplay the potential risks in favour of the benefits that was observed in a recent survey amongst US surgeons. 88 As with most minimally invasive surgical techniques, a great deal of training and skill is required in order to be able to enjoy the advantages and avoid the potentially catastrophic complications. The learning curve is inevitable, as with any new skill or technique, and the early results appear to be surgeon-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…9 Systematic reviews of this limited evidence base found no differences in patient function or complication rates between approaches. [5][6][7][8] Nevertheless, media reports 10 and surgeon promotion 11 of better outcomes with the anterior approach have been widespread and performance of anterior THAs in the United States was estimated to have increased from 12% in 2009 to 40% in 2018. 4 Reflecting technical evolution in the anterior approach and public interest in the procedure, in 2015 the Canadian Institute for Health Information began identifying the surgical approach used to conduct each THA in the country.…”
mentioning
confidence: 99%
“…Over 70% of patients who have heard of the direct anterior approach believe it is the best approach for THA because they perceive that it causes less pain and less muscle damage [8]. Surgeons also promote anterior approach THA, as a review of American Association of Hip and Knee Surgeons members found that 22.8% have websites touting the benefits of anterior approach hip replacements [9].…”
Section: Discussionmentioning
confidence: 99%